Embedded Virtual Simulator for Vehicle Powertrain Studies - Mohd Dali, Muhamad Anisrudien (2017)
The main focus of this study is to develop a LabVIEW-based program which interfaces with and employs full functionality of existing MATLAB-based Advanced Vehicle Simulator (ADVISOR) powertrain software for powertrain analysis and simulation. The purpose of developing this project is strictly to enable beginners and intermediates to study and understand the benefits and drawbacks of different types of vehicle powertrains besides provide an alternative that can be accessible to the public as most of the software available for powertrain analysis and simulation are only accessible to engineers and powertrain specialists. This platform was designed to provide a more dynamic simulation environment, thus enable users with all levels of skills and knowledge to easily perform an analysis and simulation on vehicle powertrain. NI Single Board RIO or known as NI sbRIO is used in this simulator to develop a NI-based embedded platform to connect to external hardware and I/O, thus detailed analysis and simulation of user defined drivetrain components can be implemented.